No ordinary consultation – a qualitative inquiry of hospital palliative care consultation services. Issue 6 (4th August 2020) - Böling, Susanna; Berlin, Johan M.; Berglund, Helene; Öhlén, Joakim
Abstract : Purpose: Considering the great need for palliative care in hospitals, it is essential for hospital staff to have palliative care knowledge. Palliative consultations have been shown to have positive effects on in-hospital care. However, barriers to contact with and uptake of palliative consultation advice are reported, posing a need for further knowledge about the process of palliative consultations. The purpose of this study therefore was to examine how palliative consultations in hospitals are practised, as perceived by consultants and health care professionals on receiving wards. Design/methodology/approach: Focus groups with palliative care consultation services, health care personnel from receiving wards and managers of consultation services. Interpretive description and constant comparative method guided the analysis. Findings: Variations were seen in several aspects of practice, including approach to practice and represented professions. The palliative consultants were perceived to contribute by creating space for palliative care, adding palliative knowledge and approach, enhancing cooperation and creating opportunity to ameliorate transition. Based on a perception of carrying valuable perspectives and knowledge, a number of consultation services utilised proactive practices that took the initiative in relation to the receiving wards. Originality/value: A lack of policy and divergent views on how to conceptualise palliative care appeared to be associated with variations in consultation practices, tentative approaches and a bottom-up driven development. This study adds knowledge, implying theoretical transferability as to how palliative care consultations can be practised, which is useful when designing and starting new consultation services.